MATURATION AND FECUNDITY OF MUDSKIPPER BOLEOPHTHALMUS DENTATUS IN THE NORTHERN ARABIAN SEA - Hoda, S M Shamsul; Akhtar, Yasmin (Indian Journal of Fisheries, 2011)
Seven maturity stages are described in the development of gonads in the mudskipper, Boleophthalmiis dentatus Cuv. Val. from Karachi. The mean length at first maturity, 69 mm SL in males and 72 mm SL in females, is supported by gonosomatic index (GSI), hepatosomatic index (HSI) and condition factor (K). A sex ratio of 1.04 male : 1.00 female is observed. Length-frequency curves indicate that the juveniles and young found in September to December are the products of the same year and the juveniles measuring 45 mm SL in September increases to 60 mm SL within three months. The ova-diameter polygons Indicate that the spawning of individuals occurs twice during the period from April to December, April-May and July-August. The mean fecundity is 2371; variation being 970 at 75 mm SL to 4113 at 110 mm SL. Fecunditystandard length, fecundity-total fish weight and fecundity-ovary weight relationships are presented